Exploring women, gun ownership, and gender - Whitney, Cindy (Kansas State University, 2015)
How and why individuals choose to become gun owners is a complicated issue. Historically, in America, firearms have been associated with patriotism, citizenship, and freedom. Also, historically, much of the research on gun owners has primarily focused on males. Despite the fact that many women do, indeed, own firearms; women, even today, are still often considered an anomaly when it comes to owning guns and participating in the shooting sports. This research utilized an historical analysis, direct interviews with female gun owners, and participation-observation at National Rifle Association (NRA) sponsored Women on Target events, to explore and examine how and why women become owners; as well as how they negotiate the often masculine world of the shooting sports. The data is analyzed through a gender lens, primarily focusing on doing gender, othering, and boundary maintenance. Findings show that firearms ownership is a complex issue and that stereotypical gender believes strongly influences the interaction and images of men and women shooters alike.
Keywords: Women; Gender; Guns; Sociology (0626)